Accelerated and long-term ageing of natural rubber vulcanisates - Baker L R (Journal of Natural Rubber Research, 1987)
The influence of temperature on oven-ageing performance has been studied using black-filled natural rubber (NR) compounds vulcanized with conventional, semi-EV, EV and mixed Novor/sulphur-curing systems. Time to 80;retention of tensile strength during ageing was found to follow an Arrhenius type relationship and this was used to modify time scales so that changes in other properties at various temperatures could be compared. Changing the ageing temperature had the effect of altering relative resistance to degradation among the test compounds. Modulus increases, particularly with the conventionally cured compound, were found to be less at 100 degree C than at lower temperatures. Each observation that, for a Novor-curing system, ageing at 100 degree C gave a tendency to both a higher tension fatigue life and an increase in modulus was confirmed for ageing at 50 degree C.
Keywords: Ageing; Natural rubber vulcanisates